INVESTIGATIONS USING CSIRO HI TRIAXIAL CELLS FOR MEASURING THE STRESS STATES OF ROCK MASSES SUBJECT TO MINING EXTRACTION: NUMERICAL MODELLING OF IN-SITU EXTRACTED CORE SAMPLES - De Lucia, Vivien; Ermini, Andrea; Guido, Stefano; Marchetti, Daria; Gullì, Domenico; Salvini, Riccardo (Italian journal of engineering geology and environment, 2024)
the measurement of the stress state of rock, carried out in-situ using the overcoring CSIro hI Cell technique, provides valuable information about the rock mass geo-structural and stress conditions. this is particularly useful for calibrating the numerical model of natural slopes and excavations fronts and for assessing their static conditions. thus, it allows to improve workplace safety conditions in both open-pit and underground quarries. During an in-situ CSIro test, the stress release strains are measured by 12 strain gauges differently oriented in the space and the stress tensor and the material elastic parameters are then computed. the classic interpretative procedure of stress release test refers to analytical formulations that assume an extracted sample of regular cylindrical shape. however, during overcoring, it may happen that a discontinuity is intercepted, causing the extracted core to break and to assume an irregular shape. to address this challenge, in this work, a Finite Element numerical simulation of stress release was conducted basing on a 3D digital model of the irregular sample resulting from a Photogrammetric Survey. this allowed for the computation of the stress tensor for both irregularly shaped and ideal cylindrical samples. the research proceeded as it follows: i) three-dimensional modelling of the irregularly shaped core using Photogrammetric techniques and mesh Editing, which enabled the accurate representation of complex geometries; ii) numerical modelling of the irregularly shaped core containing the CSIro hI Cell through Finite Element Analysis, providing insights about stress and deformation distributions; iii) stress State of the rock calculation using a multiple Linear regression Procedure by using the coefficient matrix as determined by the core numerical modelling. the implementation of this procedure may facilitate the determination of stress state for irregularly shaped cores, and it enhances to understand how shape and rock elastic properties may influence the stress release behaviour. this comprehensive approach could allow to address challenges associated to stress assessment for irregular shaped rock cores and to improve the accuracy and applicability of geotechnical engineering methods.